EW[OIII] as an Orientation Indicator for Quasars: Implications for the Torus - Bisogni, Susanna; Marconi, Alessandro; Risaliti, Guido; Lusso, Elisabeta (Frontiers in Astronomy and Space Sciences, 2017)
We present an analysis of the average spectral properties of 12,000 SDSS quasars as a function of accretion disc inclination, as measured from the equivalent width of the [O III] 5007Å line. The use of this indicator on a large sample of quasars from the SDSS DR7 has proven the presence of orientation effects on the features of UV/optical spectra, confirming the presence of outflows in the NLR gas and that the geometry of the BLR is disc-like. Relying on the goodness of this indicator, we are now using it to investigate other bands/components of AGN. Specifically, the study of the UV/optical/IR SED of the same sample provides information on the obscuring “torus”. The SED shows a decrease of the IR fraction moving from face-on to edge-on sources, in agreement with models where the torus is co-axial with the accretion disc. Moreover, the fact we are able to observe the broad emission lines also in sources in an edge-on position, suggests that the torus is rather clumpy than smooth as in the Unified Model. The behaviour of the SED as a function of EW[OIII] is in agreement with the predictions of the clumpy torus models as well.